Konversi Kayu Ketapang (Terminalia Catappa. L) Menjadi Bio-Oil Menggunakan Metode Pirolisis Dengan Katalis Co-Mo/NZA - Rizky, Muhammad; Bahri, Syaiful; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The demand of fossil fuel is increasing each year. On the other hand, the availability of conventional petroleum fuels diminishing due to its non-renewable. Therefore, it is necessary to develop a new alternative fuel that can be renewed, one of the solution is the processing of biomass into bio-oil. Bio-oil is a result of the pyrolysis of biomass. Availability of Ketapang rod is converted into bio-oil by pyrolysis method using catalysts natural zeolite. The purpose of this study was to determine the performance of the catalyst to produce bio-oil, characterize the density, viscosity, acid number, and flash point of bio-oil that produced, as well as analyze the chemical components of bio-oil by GC-MS method. Pyrolysis of Ketapang rod catalyst from natural zeolite in the reactor slurry do by feeding 50 grams with the size -100 +200 mesh, silinap 500 ml, stirring speed is set to 300 rpm, 320oC temperature, and the process runs for 120 minutes. The results showed that the optimum yield obtained on 2.5% catalyst, amounting to 77%. The test results obtained by the physical properties of density 0.875 g/ml, 9.56 cSt viscosity, acid number of 49,89 gr NaOH/gr sample. Keywords: Bio-oil, pyrolysis, Ketapang rod, natural zeolite, alternative fuels